Relationships between soil moisture content and root morphology of three herbs on alpine scoria desert of Mt. Fuji. - Anisuzzaman, G.M.; Nakano, Takashi; Masuzawa, Takehiro (National Institute of Polar Research, 2002)
P(論文) Artemisia pedunculosa, Polygonum cuspidatum and P. weyrichii are codominant species on the Hoei second crater of Mt. Fuji. The aim of this study is to describe root systems and the relationship between soil moisture and root morphology of these species. Most of the root distribution of A. pedunculosa was restricted within 20cm depth and was widely spread in the surface soil. More than 1m vertical and shorter horizontal root extension was found for the latter two species. The fine root mass per leaf area (FRMLA) of A. pedunculosa was more than 7 times and 3 times greater than these of P. weyrichii and P. cuspidatum, respectively. From the above results, A. pedunculosa depends on a large area of surface soil water, while the two Polygonum species depend on deep-layer soil water. The vertical root extension of the two Polygonum species is assumed to support their establishment on slope sites where surface soil movement is frequent and moisture content is low. departmental bulletin paper